2019
DOI: 10.1002/epi4.12317
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Anakinra in the relapsing chronic phase of febrile infection–related epilepsy syndrome

Abstract: Summary Febrile infection–related epilepsy syndrome (FIRES) is a severe epileptic encephalopathy with presumed inflammatory origin and lacking effective treatments. Anakinra is the human recombinant interleukin 1 receptor antagonist clinically used in autoinflammatory or autoimmune conditions. We report a case of FIRES for which the spatial and temporal match between electroencephalography (EEG) and magnetic resonance imaging (MRI) focal alterations provides support for the detrimental synergic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 16 publications
3
108
0
Order By: Relevance
“…Interference of the IL‐1β proinflammatory cascade has been shown to decrease seizure frequency, whereas amplification of this pathway has been reported to cause worsening of seizures and a worse outcome in animal models . Although there are early reports of effect of anakinra (IL‐1R antagonist) and tacrolimus (targeting T cells) in reducing the severity of FIRES in experimental models and case reports, more data are needed to determine whether this inflammatory process is modifiable …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interference of the IL‐1β proinflammatory cascade has been shown to decrease seizure frequency, whereas amplification of this pathway has been reported to cause worsening of seizures and a worse outcome in animal models . Although there are early reports of effect of anakinra (IL‐1R antagonist) and tacrolimus (targeting T cells) in reducing the severity of FIRES in experimental models and case reports, more data are needed to determine whether this inflammatory process is modifiable …”
Section: Discussionmentioning
confidence: 99%
“…53 Although there are early reports of effect of anakinra (IL-1R antagonist) and tacrolimus (target ing T cells) in reducing the severity of FIRES in experimental models and case reports, more data are needed to determine whether this inflammatory process is modifiable. 10,27,54,55 A strength of our study is that we studied cytokines/ chemokines in acute CSF samples of FIRES/FRD and fe brile and afebrile status epilepticus groups, and compared these with chronic epilepsy subgroups with ongoing fre quent daily seizures. The fact that FSE and ASE had a similar duration and severity of seizures allowed us to compare the effects of "seizures themselves" on inflam mation.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β drives the pathologic role of brain inflammation in epilepsy . Studies on surgically resected epileptogenic foci from drug‐resistant forms of epilepsy with structural or infectious etiologies showed that the IL‐1α–IL‐1R1 axis is activated in neurons, glia, and endothelial cells of the BBB .…”
Section: Anakinramentioning
confidence: 99%
“…IL-1β drives the pathologic role of brain inflammation in epilepsy. [104][105][106][107][108][109][110][111][112] Studies on surgically resected epileptogenic foci from drug-resistant forms of epilepsy with structural or infectious etiologies showed that the IL-1α-IL-1R1 axis is activated in neurons, glia, and endothelial cells of the BBB. 104,107,[113][114][115] Similar findings were reported in animal models of acute symptomatic seizures, febrile and nonfebrile SE, and models of acquired epilepsies, 107,114 absence epilepsy, and progressive myoclonic epilepsy.…”
Section: Anakinramentioning
confidence: 99%
“…In contrast, administration of the IL-1R antagonist is anticonvulsive (Heida and Pittman, 2005), while IL-1R-deficient mice are resistant to FS, independent of the genetic background strain (C57Bl or 129/Sv) (Dube et al, 2005). This mechanism holds strong promise for clinical translation, with two case reports demonstrating that treatment with the IL-1R antagonist reduced seizure burden and relapse in children with febrile infection-related epilepsy syndrome (Kenney-Jung et al, 2016;Dilena et al, 2019).…”
Section: Hyperthermia-induced Febrile Seizuresmentioning
confidence: 99%